2015
DOI: 10.7763/joebm.2015.v3.172
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Economic Freedom on National Competitiveness: Causality from a Panel of Countries

Abstract: Abstract-The paper deals with economic freedom and its effect on national competitiveness. There are two goals examined within the paper. At first, I examine if economic freedom causes national competitiveness by means of the Granger causality test. Secondly, the effect of economic freedom on national competitiveness is tested using panel data for the period 2004-2011. Three groups of countries were selected: economic free, Visegrad four and repressed countries. Economic freedom and national competitiveness ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Those results are in accordance with Mihaela (2016), Petrariu, Robert, andRadu (2013), Chung (2011), Verner (2015, Pilinkiene (2016), & Webster and Stanislav (2014) who shows that the results show that the country's competitiveness has a positive and significant effect on economic growth. Dkhili and Lassad (2018), Alzaidy, Mohd and Zakaria (2017), Mehdi (2012), Riyad (2012), Alfaro, Areendam, Sebnem, and Selin (2010), Alfaro, Areendam, Sebnem, and Selin (2004), and Alfaro (2003) who show that Foreign Direct Investment has a positive and significant effect on economic growth.…”
Section: Random Effect Model Regression Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Those results are in accordance with Mihaela (2016), Petrariu, Robert, andRadu (2013), Chung (2011), Verner (2015, Pilinkiene (2016), & Webster and Stanislav (2014) who shows that the results show that the country's competitiveness has a positive and significant effect on economic growth. Dkhili and Lassad (2018), Alzaidy, Mohd and Zakaria (2017), Mehdi (2012), Riyad (2012), Alfaro, Areendam, Sebnem, and Selin (2010), Alfaro, Areendam, Sebnem, and Selin (2004), and Alfaro (2003) who show that Foreign Direct Investment has a positive and significant effect on economic growth.…”
Section: Random Effect Model Regression Resultssupporting
confidence: 87%
“…There are several studies that have been carried out to examine daylight, corruption perception index, and Foreign Direct Investment on economic growth including: Mihaela (2016), Petrariu, Ioan R, Robert Bumbac, and Radu Ciobanu (2013), Chung (2011), Verner (2015, Pilinkiene (2016), and Webster, Craig and Stanislav Ivanov (2014) who examined the country's competitiveness towards economic growth. The results showed that the results showed that the country's competitiveness had a positive and significant effect on economic growth.…”
Section: Empirical Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…G7 countries enjoy higher levels of political and economic freedoms, better governance, and less corruption than their counterparts in emerging markets. The findings of a panel study of countries showed that economic freedom is positively related to national competitiveness (Verner 2015). A survey of business managers found that political and economic freedoms are regarded as important drivers of competitiveness in Hong Kong.…”
Section: H6mentioning
confidence: 99%
“…This is due to the fact that economic opening is only bene cial for economies which are able to impose themselves both on the domestic and external market. (Verner, 2015). This challenge is particularly important for the member countries of the West African Economic and Monetary Union (WAEMU) which for several decades have suffered from a lack of competitiveness on a regional and international scale (Dumont and Mesple-Somps, 2000).…”
Section: Introductionmentioning
confidence: 99%